Effect of embryo density and microdrop volume on the blastocyst development of mouse two-cell embryos - Teraporn Vutyavanich (2018)
Objective: To study the effect of embryo density and microdrop volume on mouse two-cell embryo development. Design: Experimental study. Setting: Assisted conception laboratory. Animal(s): Two-cell mouse embryos (n = 1511). Intervention(s): One, five, 10, or 15 embryos were cultured in 10-μL drops of cleavage medium. In the second study, embryos were cultured singly in 0.5-, 1-, 2-, 5-, and 10-μL drops. Finally, they were cultured in pair in 0.5-, 1-, and 2-μL drops. After 48 hours, embryos were transferred into blastocyst medium for an additional 24 hours. Main Outcome Measure(s): Cleavage and blastocyst formation and inner cell mass (ICM) and trophectoderm (TE) cell numbers. Result(s): No differences in cleavage or blastocyst formation were found in different groups in experiment 1, 2, or 3. Embryos cultured singly had fewer ICM and TE cells than those cultured in groups. Embryos cultured singly in 0.5 μL had fewer TE cells than those in 10 μL, but had insignificant difference in the ICM. Duo culture in 0.5-2 μL appeared to give the same results as group culture in 10-μL drops. Conclusion(s): Group culture is preferred when using sequential media. Beneficial effects cannot be mimicked by volume reduction in single-embryo culture. © 2011 American Society for Reproductive Medicine, Published by Elsevier Inc.